Pelatihan Pembuatan Bahan Ajar Berbasis Literasi, Numerasi dan Karakter Bagi Guru SMP Swasta PAB Se-Kabupaten Deli Serdang - Syahrina Anisa Pulungan; Fira Astika Wanhar; Fatmawati Fatmawati; Dian Arianto (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
The lack of teacher knowledge related to numeracy and character literacy, the low ability of numeracy literacy and student character and the low ability of teachers in developing numeracy and character literacy-based teaching materials so that the achievement of learning objectives is still low, on the other hand the 2013 Curriculum mandates numeracy and character literacy-based learning. The solution to overcome the existing problems can be through training for mathematics teachers at PAB Private Junior High Schools, namely the manufacture of teaching materials based on numeracy and character literacy. Specific targets that are expected to be achieved through this service program are improving the quality of learning, increasing pedagogic competence and developing the professionalism of mathematics teachers. For this reason, this activity will provide skills training in the development of numeracy and character-based teaching materials according to the interests of partners, so that later partners are able to develop and apply numeracy and character-based teaching materials in classroom learning so as to improve numeracy literacy skills and the character of teachers and students.